Indirect measurement of frother concentration based on l-CCC curves. (June 2016) - Kracht, W.; Hunt, C.
Highlights: l - CCC curves are used to determine frother concentration. The technique is validated against the total organic carbon (TOC) method. The measurements are not affected by the presence of xanthate in the system. Abstract: The local critical coalescence concentration l - CCC presents a relationship between frother concentration and the gas flow rate Q g ′ at which coalescence starts to occur at a capillary tube. Such a relationship is used in this work to determine frother concentration. The solution with unknown frother concentration is tested to determine Q g ′ and the concentration is determined from a reference l - CCC curve that has been previously determined for the frother to be tested. The technique is simple, and easy to implement. The determination of the reference l - CCC curve takes 1 h or less, after which the measurements are very quick, taking no more than 5 min per sample. The technique was validated against the total organic carbon (TOC) method for a series of samples of unknown frother concentration, for three different frothers, with a correlation coefficient R 2 equal to 0.997. The measurements are not affected by the presence of xanthate in the system, when using MIBC as a frother, which suggests the possibility of using it, combined with TOC analysis to determine both frother and xanthate concentration by mass balancing.